KRITIK SOSIAL DALAM LIRIK LAGU IWAN FALS PERIODE TAHUN 1980-1992 - Wijaya, Ronald Albert Michael; shoim, m (Universitas PGRI Adi Buana Surabaya, 2014)
Abstract Language is sign system first level, which already has a meaning (Meaning). In this language literature meaning elevated to meaning (significance) as sign system second level. Music is a means of cultures present in the community as the construction of social reality embodied in the form of song lyrics. In principle, the lyrics of the song to express the reality of life. Lyrics of Iwan Fals’s song quite different, because Iwan fals did not question the class but more critical of a particular class or practice that does oppression injustice. Data collected in the form Iwan Fals lyric song. Data collection is done by listening to the Iwan Fals song, then transcribe the lyrics Iwan Fals. The results obtained from research in the social criticism in the lyrics of the Iwan Fals’s song can be concluded that each Iwan Fals’s song always reflect the social conditions that occur when the lyrics created, as on the lyrics kisah motorku, sarjana muda, guru umar bakri, tak biru lagi lautku, isi rimba tak ada tempat berpijak lagi, kereta tiba pukul berapa, siang seberang istana, sore tugu pancoran, ujung aspal pondok gede, tikus kantor, lancer, surat buat wakil rakyat, bongkar, bento, dan mereka ada dijalan. Key Words : Language, Lyric Song, Social Criticism